ANALISIS KEMAMPUAN PEMECAHAN MASALAH MATEMATIK SISWA MTS KELAS IX PADA MATERI BILANGAN BERPANGKAT DAN BENTUK AKAR - Riska Nurvela; Wahyu Setiawan (Departement of Mathematics Education, 2019)
Problem solving is a problem that is very useful for students and helps students in living their daily lives. Students need to solve problems so that later students can think systematically, logically, and critically, and persistently in solving problems in life that they face especially in basic mathematical learning. this study was to analyze the ability of mathematical problem solving students of MTS class IX on material number and root shape. This type of research is a qualitative descriptive study. by means of midterm research data collection (PTS) which is then analyzed qualitatively. The population is MTS class IX A students with many students 31 people, the results of this study indicate that students can answer correctly, medium and wrong in answering questions. The category of students 'ability to solve the problem of numbered numbers and root shapes where the results of this study show that 9 students can answer questions correctly, while 8 students answer questions incorrectly and 14 students answer incorrectly, the categories of students' abilities in problem solving are low. This is shown 9 Answering the question correctly, 14 answering the question incorrectly and 8 answering the question incorrectly. The research instruments used for the study were round number and root mathematical problems with five questions. Because the students 'difficulties in working on the questions in counting, the other difficulty is that students do not understand the concept of numbered numbers and root shapes, it causes them to wrongly work on and conclude questions about numbered numbers because of students' difficulties in calculating questions in calculating. the concept of rank and root form,